Planning of Energy Saving with Cogeneration System - Imam Abdul Rozaq; NYD Setyaningsih; Budi Gunawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
PT Dua Kelinci is one of the largest food industries in Pati Regency one of whose products is egg peanut which needs huge electric and heat energy so that energy saving needs to be done. One of the efforts of energy saving is by conducting cogeneration (merging between electric and heat). This research started from a data collection, i.e. finding out the need of electricity and heat in the process of egg-peanut manufacture by a cogeneration technology at PT Dua Kelinci. The research method includes technical analysis and economic analysis. From the technical analysis, it is found that the electric energy saving by using cogeneration 103.680 kW and the heat energy saving is 4,075 TJ/year. From the economic analysis it is seen that before using cogeneration the cost that should be expended is USD 75.209,61 while after using cogeneration the cost is USD 60.6014,04 therefore from the economic aspect there is energy saving as much as USD 15.19,57/year.